Modern Materials for Non-Viral Delivery Systems in Gene Therapy - Radnaeva, A.V.; Slobodkina, E.A.; Tkachuk, V.A.; Makarevich, P.I. (Biomedical Chemistry: Research and Methods, 2026)
Modern gene delivery systems are classified into viral and non-viral vectors. Despite the predominance of viral vectors in gene therapy drug development due to their high transduction efficiency, their application is limited by immunogenicity, the risk of insertional mutagenesis, and inflammatory responses. Non-viral systems offer a superior safety profile, scalable manufacturing potential, and flexibility in genetic cargo loading but are less effective in transfection efficiency. The main challenges affecting non-viral vector transfection include the low stability of nucleic acids in vivo, problems in delivering the genetic material into the cell nucleus, and the toxicity of chemical components within the vector design. To overcome the low delivery efficiency of genetic material by non-viral vector systems, further research should focus on optimizing the chemical structure of carrier molecules, their modification to enhance targeting, and detailed investigation of intracellular vector transport pathways. Currently, the most promising application areas for non-viral delivery systems are oncology, vaccine development, and pulmonary diseases.